Design of Jominy Hardenability Testing Equipment in Accordance with ASTM A255 Standard - Muhammad Isdy, Rizky; Listyanda, R. Faiz; Kussuma Hadi Sufyan, M. Fendy; Tafga Arfanindita, Her; Taufik, Ikhwan (Jurnal Rekayasa Mesin, 2025)
This study discusses the design and development of a Jominy Hardenability Test apparatus based on the ASTM A255 standard, which is used to determine the hardenability of metallic materials, particularly steel. The purpose of this research is to produce a Jominy testing device that meets standard specifications, perform structural analysis using CAD Software, and evaluate the functional performance of the manufactured tool. The research method consists of several stages, including 3D design using CAD Software, structural analysis simulation with the Finite Element Analysis (FEA) method covering von Mises stress, displacement, and safety factor, followed by the manufacturing process according to the design results. The simulation results show a maximum stress of 2.039 × 106 N/m², a maximum displacement of 5.8 × 10⁻¹ mm, and a safety factor value of 2.6, indicating that the design is structurally safe for production. The manufacturing process uses galvanized as the frame, body material and includes an additional cooling fan to maintain water temperature stability during the quenching process. The functional test results show that the tool can perform quenching effectively, producing a maximum hardness value of 370 VHN and a minimum value of 280 VHN on the steel specimen. This research is expected to contribute as a reference for the development of economical, efficient, and standard ASTM A255 compliant Jominy testing equipment for researh and development.